Effective Use of Web-Based Credential Method for Radiographers - Wahyuni, Wilda; Adi, Kusworo; Wibowo, Gatot Murti; Hariri, Ahmad (Jurnal Multidisiplin Madani, 2023)
The radiographer credential is an evaluation process to determine the eligibility of clinical privilege granted to radiographers. This study aims to determine the effectiveness of the web-based radiographer credential method that has been developed by hospital IT. The method used was qualitative descriptive with the distribution of questionnaires to users of 25 respondents. The research variables used were system quality, information quality, service quality, user intention, user satisfaction and net benefit with a pre-experimental design of one group pre and post test Wilcoxson test. The effectiveness test results of the web-based radiogafer credential method are very effective with Asymp.Sig. (2-tailed) 0.000 (<0.05). This shows that web-based Credential Applications are very good and effective utilization